Learn Java for Android Development - Friesen, Jeff JavaJeff . (Apress, 2010)
Android development is hot, and many programmers are interested in joining the fun. However, because this technology is based on Java, you should first obtain a solid grasp of the Java language and its foundational APIs to improve your chances of succeeding as an Android app developer. After all, you will be busy learning the architecture of an Android app, the various Android-specific APIs, and Android-specific tools. If you do not already know Java fundamentals, you will probably end up with a massive headache from also having to quickly cram those fundamentals into your knowledge base. Learn Java for Android Development teaches programmers of any skill level the essential Java language and foundational Java API skills that must be learned to improve the programmers chances of succeeding as an Android app developer. Each of the books 10 chapters provides an exercise section that gives you the opportunity to reinforce your understanding of the chapters material. Answers to the books more than 300 exercises are provided in an appendix. Additionally, author Jeff Friesen has created six bonus chapters that you can download from his personal site, located at http://tutortutor.ca/cgi-bin/makepage.cgi?/books/ljfad. Once you complete this book, you will be ready to dive into Android, and you can start that journey by obtaining a copy of Beginning Android 2.